2000
DOI: 10.1038/35003555
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic evidence for a low slip rate in the Altyn Tagh fault system

Abstract: The collision between India and Asia has been simulated with a variety of computational models that describe or predict the motions of the main faults of east Asia. Geological slip-rate estimates of 20-30 mm yr(-1) suggest that the largest of these faults, the 2,000-km-long Altyn Tagh fault system on the northern edge of the Tibetan plateau, absorbs as much of the Indo-Asian convergence signal as do the Himalayas--partly by oblique slip and partly by contraction and mountain growth. However, the predictions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
200
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(229 citation statements)
references
References 21 publications
27
200
2
Order By: Relevance
“…Late Quaternary slip rates have been reported along most of the ATF at both decadal and millennial time scales. Geodetic measurements at the decadal time scale indicating that the ATF slips at~10 mm/year [12][13][14][15] have been used to support continuum deformation of the Tibetan Plateau [1,2,8,15] or block-like deformation [3,4]. Elliott et al [16] investigated the same location as this study using ERS data and the stacking method and concluded that the slip rate was 11˘5 mm/year, Remote Sens.…”
Section: Introductionmentioning
confidence: 99%
“…Late Quaternary slip rates have been reported along most of the ATF at both decadal and millennial time scales. Geodetic measurements at the decadal time scale indicating that the ATF slips at~10 mm/year [12][13][14][15] have been used to support continuum deformation of the Tibetan Plateau [1,2,8,15] or block-like deformation [3,4]. Elliott et al [16] investigated the same location as this study using ERS data and the stacking method and concluded that the slip rate was 11˘5 mm/year, Remote Sens.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson and Segall (2004) also extended the Savage and Prescott (1978) model to include the localized creep on a linear viscous shear zone within the upper elastic layer. Geographic distribution of the 15 strike-slip faults considered in this study: (1) Alpine, (2) Altyn Tagh, (3) Dead Sea, (4) Elsinore, (5) Fairweather, (6) Garlock, (7) Karakoram, (8) SAF-Mojave, (9) North Anatolian, (10) Owens Valley, (11) Philippine, (12) SAF-Carrizo, (13) SAF-Indio, (14) San Jacinto, and (15) Haiyuan (Sharp, 1967(Sharp, , 1981Savage and Burford, 1973;Plafker et al, 1978;Sieh and Jahns, 1984;Lubetkin and Clark, 1988;Rockwell et al, 1990;Barrier et al, 1991;Lisowski et al, 1991;Merifield et al, 1991;McGill and Sieh, 1993;Beanland and Clark, 1994;Duquesnoy et al, 1994;Petersen and Wesnousky, 1994;Bennett et al, 1996Bennett et al, , 1997Armijo et al, 1999;Beavan et al, 1999;Lasserre et al, 1999;Bendick et al, 2000;Klinger et al, 2000;Reilinger et al, 2000;Argus and Gordon, 2001;Lee et al, 2001;Miller et al, 2001;Niemi et al, 2001;Norris and Cooper, 2001;Banerjee and Bürgmann, 2002;Brown et al, 2002;Hubert-Ferrari et al, 2002;Fletcher and Freymueller, 2003;Meghraoui et al, 2003;Lacassin et al, 2004;…”
Section: Constraining Time-dependent Earthquake-cycle Modelsmentioning
confidence: 99%
“…They are either used to directly calculate a rate based upon a profile across the fault (Bendick et al 2000) or used in larger plateau-wide studies Gan et al 2007). Additionally, they are used in block or continuum models for the plateau (e.g.…”
Section: Gps Measurements In Tibetmentioning
confidence: 99%
“…Zhang et al 2004;Gan et al 2007), and are determined from fitting the horizontal velocities to a locked fault elastic model. The first GPS measurement for the Altyn Tagh was made by Bendick et al (2000) and consisted of a transect of GPS observations on the east-central portion of the fault and the North Altyn Tagh Fault. The result pointed towards a low slip rate of 4-14 mm a À1 (as well as a small convergent component of 2-4 mm a À1 ).…”
Section: Geodetically Modelled Slip Ratesmentioning
confidence: 99%